Schedule of Activities and Programs (Symphony in the Flint Hills, 2014)
This section includes the schedule of activities, program notes, information about the Kansas City Symphony and the conductor Aram Demirjian, and other notes of the 2014 Symphony in the Flint Hills..
Keywords: prairie art; heritage and culture presentations; program; symphony; music; Kansas City Symphony; Aram Demirjian